FORENSIC ANALYSIS ON DISTRIBUTED DENIAL OF SERVICE ATTACK ON IOT ENVIRONMENT - Fadzil H.S.; Ibrahim Z.-A.; Rahim F.A.; Sharul Nizam S.A.; Mohd Abdullah H.I.; Mustaffa M.Z. (Little Lion Scientific, 2023)
The Distributed Denial of Service (DDoS) attack is a malicious attempt to render the users unable to access a server service, usually by temporarily disabling or suspending its hosting server services. With the increase popularity of IoT devices such as the massive deployment of smart meter in Advance Metering Infrastructure, can create a situation where attacker can launch a DDoS attack in this environment. This work will focus on analyzing the impact of DDoS attack in AMI by performing data analysis from DDoS attacks that performed from IoT testbed. The testbed is use as a platform to perform the testing using multiple variation of DDoS attacks that can be launch from IoT devices. It also helps the system detect any DDoS attacks against IoT devices by tracking any abnormalities in the communication inside the testbed and connected IoT devices. 2022 Little Lion Scientific. All rights reserved.